2020
DOI: 10.1007/s12264-020-00473-y
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Effect of Increased NREM Sleep after Acute Social Defeat Stress in Mice

Abstract: Social defeat stress (SDS) plays a major role in the pathogenesis of psychiatric disorders like anxiety and depression. Sleep is generally considered to involve recovery of the brain from prior experience during wakefulness and is altered after acute SDS. However, the effect of acute SDS on sleep/wake behavior in mice varies between studies. In addition, whether sleep changes in response to stress contribute to anxiety is not well established. Here, we first investigated the effects of acute SDS on sleep/wake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The criteria used to categorize the susceptible and the resilient phenotypes vary between labs which is another potential cause for differences in findings between the various studies ( Henderson et al, 2017 ; Wells et al, 2017 ). Furthermore, several of the studies assessed the effect of acute, not chronic, social defeat stress on sleep ( Wells et al, 2017 ; Fujii et al, 2019 ; Feng et al, 2020 ) and many focused on REM sleep abnormalities in association with the depressive-like phenotype, despite observations that the diagnostic value of REM sleep abnormalities as a marker of depression has been shown to be confounded with age and gender effects ( Thase et al, 1998 ). In our study we also observed REM sleep abnormalities in terms of higher number of REM sleep bouts in the dark, pre-CSD, in mice that become susceptible to stress ( p = 0.056) and augmented REM sleep rebound, following SD, in the susceptible mice, post-CSD.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria used to categorize the susceptible and the resilient phenotypes vary between labs which is another potential cause for differences in findings between the various studies ( Henderson et al, 2017 ; Wells et al, 2017 ). Furthermore, several of the studies assessed the effect of acute, not chronic, social defeat stress on sleep ( Wells et al, 2017 ; Fujii et al, 2019 ; Feng et al, 2020 ) and many focused on REM sleep abnormalities in association with the depressive-like phenotype, despite observations that the diagnostic value of REM sleep abnormalities as a marker of depression has been shown to be confounded with age and gender effects ( Thase et al, 1998 ). In our study we also observed REM sleep abnormalities in terms of higher number of REM sleep bouts in the dark, pre-CSD, in mice that become susceptible to stress ( p = 0.056) and augmented REM sleep rebound, following SD, in the susceptible mice, post-CSD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the function and benefits of sleep remain unclear, sleep is certainly restorative ( 10 ). Thus, sleep has been suggested to be one of the mechanisms for alleviating the malign effects of stress ( 4 , 9 , 11 , 12 ). Whether a specific circuit links stress and sleep is, however, unknown.…”
mentioning
confidence: 99%
“…Sleep architecture is significantly altered in sleep disorders, mood disorders, and infectious diseases ( Besedovsky et al, 2019 ; Irwin, 2019 ; Atrooz and Salim, 2020 ). Epidemiological studies have shown that sleep deficiency is associated with inflammation, neuropsychiatric diseases, and multi-organ injury ( Leproult et al, 2014 ; Irwin et al, 2016 ; Atrooz and Salim, 2020 ; Feng et al, 2020 ; Ramos-Lopez et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%